Antibiotic Resistance: Situation Analysis In a Tertiary Care Hospital of Bangladesh (Bangladesh Journal of Microbiology, 2018)
Emergence of multidrug resistant organism (MDR) is a global concern. Resistance pattern of organism varies from one country to another and within the country. Systematic data are lacking in many developing countries of the world. In view of the above, the present study was undertaken to investigate the current situation of antibiotic resistance and patterns of organism responsible for major infection in a seven hundred bed tertiary care hospital of Bangladesh. A total of 27,069 clinical samples collected over four years period (2011 to 2014) were included in the study. The samples were cultured in respective media as per standard procedure. Identification of organism and antibiotic sensitivity was performed according to CLSI guidelines. All data were analyzed by Whonet-5 software. Out of 27,069 clinical samples, urine was 59.7%, blood was 25.1%, pus/ wound swab was 7.9% and respiratory sample was 7.2%. Growth was obtained in 27.3% of the total sample. 28% urine, 8% blood, 66% pus and wound swab and 42% respiratory sample were found culture positive. Major Gram negative bacteria namely Escherichia coli, Klebsiella sp., Salmonella sp., Pseudomonas sp. and Acinetobacter sp. were 22,119 and major Gram positive bacteria namely Staphylococcus aureus and Enterococcus sp were 4353 in overall culture positive sample. The major Gram negative bacteria showed resistance to imipenem (3 -84%), third generation cephalosporin (61.6%-94.9%), aminoglycosides (10.8-88.6%), ciprofloxacin (56-90.1%), cotrimoxazole (58-80.3%), nitrofurantoin (14.3-91.7%), tazobactum+piperacillin (20.8-81.4% ) and colistin (2.2- 16.4%). The carbapenem resistant enterobacteriaceae (CRE) was 9.8%. ESBL positivity rate among Escherichia coli, Klebsiella sp., Enterobacter sp. and Citrobacter sp. were 44.8%, 31.1%, 29% and 15.4% respectively. Average ESBL producing enterobacteriaceae was 18 to 31% over four years. So there is considerable proportion of ESBL producing and imipenem resistant Gram negative bacteria. The isolation rate of MRSA was 33%. No vancomycin resistant Staphylococcus aureus (VRSA) and enterococci (VRE) was detected but 39% enterococci showed high level resistance to gentamicin (HLGRE). Of special interest, 92% Salmonella was nalidixic acid resistant (NARST).The high rate of NARST was consistant over four years. The result indicate high prevalence of resistant organisms to several antibiotics. Regular monitoring and surveillance is necessary for curbing the emergence of resistant organism and effective infection control in the hospital settings of Bangladesh.Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 15-19